Advancing Cardiovascular, Neurovascular and Renal Magnetic Resonance Imaging in Small Rodents Using Cryogenic Radiofrequency Coil Technology - Niendorf, Thoralf; Pohlmann, Andreas; Reimann, Henning M.; Waiczies, Helmar; Peper, Eva; Huelnhagen, Till; Seeliger, Erdmann; Schreiber, Adrian; Kettritz, Ralph; Strobel, Klaus; Ku, Min-Chi; Waiczies, Sonia (Frontiers in Pharmacology, 2015)
Research in pathologies of the brain, heart and kidney have gained immensely from the plethora of studies that have helped shape new methods in magnetic resonance (MR) for characterizing preclinical disease models. Methodical probing into preclinical animal models by MR is invaluable since it allows a careful interpretation and extrapolation of data derived from these models to human disease. In this review we will focus on the applications of cryogenic radiofrequency (RF) coils in small animal MR as a means of boosting image quality (e.g. by supporting MR microscopy) and making data acquisition more efficient (e.g. by reducing measuring time); both being important constituents for thorough investigational studies on animal models of disease. This review attempts to make the (bio)medical imaging, molecular medicine and pharmaceutical communities aware of this productive ferment and its outstanding significance for anatomical and functional MR in small rodents. The goal is to inspire a more intense interdisciplinary collaboration across the fields to further advance and progress non-invasive MR methods that ultimately support thorough (patho)physiological characterization of animal disease models. In this review, current and potential future applications for the RF coil technology in cardiovascular, neurovascular and renal disease will be discussed.